EFFECTIVE USE OF INNOVATION POTENTIAL OF UZBEKISTAN - Gafurova Umida Fatikhovna (Scholars Digest Publishing, 2023)
Republic of Uzbekistan Currently, innovative development is becoming the most important element of the socio-economic development of countries and regions of the world economy. In Uzbekistan, as in other countries of the world community, large-scale work is being carried out to modernize, technical and technological re-equipment of industrial production, and to involve academic and industrial science in this process. Therefore, in our country, the successful experience of states where innovation ensures the expected economic growth of the national economy must be deeply studied, analyzed, made maximum use and adapted.